Negotiating Consumerism and Feminism on Instagram - Hogsnes, Mathilde; Hansen, Kjeld (2018 IEEE Intl Conf on Parallel & Distributed Processing with Applications, Ubiquitous Computing & Communications, Big Data & Cloud Computing, Social Computing & Networking, Sustainable Computing & Communications (ISPA/IUCC/BDCloud/SocialCom/SustainCom), 2018)
In this preliminary research paper, we identify and characterize the current practices of top Norwegian female social influencers on Instagram. We introduce theories of social influence, consumerism, and new feminism to enlighten our discussion of how the social influencers exercise their influence. We present the results and analysis of the visual and textual content of 5,083 Instagram postings as well as supplementary online content. In our conclusion, we discuss the significance of the social influencers' negotiation of consumerism and feminism on Instagram as well as directions for future research.